Interiorização Industrial no Ceará : estudo comparativo da região de Sobral e CRAJUBAR - período 1985 a 2003 - Lima, Carlos Mário Holanda (2006)
The importance of a government policy focused on fostering sectors of the economy, specially the industrial sector, has played an important role in the growth process and regional economy development. In what concerns to the state of Ceará, FDI/PROVIN can be cited as the major example of a financial instrument to attract industrial projects. The government`s role in gathering and coordinating investments has been very important, mainly in areas of low economic expression and/ or lacking a basic industrial organization. The period of our research was from 1985 until 2003, and particulary attention for the sub-period 1995 – 2002, a time when the FDI/ PROVIN program was intensified. The data base was extracted by RAIS statistics, data by IPECE and FDI program. The regions studied are region 06 and region 18/19. The underlying hypothesis shows that the regional economic growth has been unequal between these two regions in focus. The methodology used involved first a descriptive analysis, making use 05 coefficients/ quotients of regional analysis such as locational quotient and others. The second tool of analysis was pooled cross section model for each region and for both considered together. The locational quotient was considered dependent variable and the workforce, potential of market and some dummies such as independents variables. The preliminary results show that industrialization process increase was different and unequal between regions 06 and 18/19. In the same way the wealth was concentrated in few cities. The Sobral region, represented at region 6, presented an industrial increase better than that in region 18/19; more cities with industrial activity than that in region 18/19. The regression model showed that the FDI impact added more strong effects in the region of Sobral(region 06) than that in the CRAJUBAR –Crato, Juazeiro e Barbalha region (region 18/19).